Efectos de la aplicación de diferentes dosis de productos orgánicos fijadores de nitrógeno atmosférico en presencia de tres densidades de siembra en el cultivo de chía (Salvia Hispánica L.) - Aldaz Riera, Angel Xavier (2016)
SUMMARY This research was conducted on the grounds of the farm "San Pablo" belonging to the Faculty of Agricultural Sciences, Technical University of Babahoyo in chia (Salvia hispanica L.) testing two biofertilizers in the presence of three population densities, with the to: a) determine the density planting more appropriate to maximize grain yield rows; b) Establishing the most appropriate of organic products fixing atmospheric nitrogen to maximize performance of chia; and c) Analyze economically treatments. Two factors were studied: a) Organic Products Noctin atmospheric nitrogen fixers in doses Azo 600; 750 and 1000 cc / ha and 450 doses Nitragin; 600 and 750 cc / ha, plus a control lacking the biofertilizer was included. Population densities were: 15; 20 and 25 plants per m2. Experimental design "split plot" was used in three repetitions; the main plots correspond to population densities (treatments) and organic nitrogen fixers (subtratamientos) as experimental subplots. The experimental subplot consisted of 4 rows of 5 m in length spaced at 0.50 m, giving an area of 10 m2; while the useful area was determined by the two central rows, leaving an area of 5 m2. variables, plant height at 30 days were evaluated after planting and beginning of the reproductive stage, number of inflorescence per plant, length of inflorescence, inflorescence weight, physiological maturity, number of plants to harvest and yield grain. All variables were subjected to analysis of variance. statistical significance test of Tukey to 95% probability was used for comparisons of mean population densities, doses of organic biofertilizers and interactions. Based on the analysis and statistical interpretation of experimental results, it was concluded: 1. Planting densities significantly influenced the characters evaluated. 2. The highest grain yield (seed) of 1268.33 kg/ha was achieved with planting density of 20 plants per square meter, exceeding 6.45 % and 17.65 % at stocking densities of 25 and 15 pl/m2, respectively. 3. The highest grain yield (seed) was obtained with planting density of 20 pl/m2 in the presence of Nitragin in doses of 750 cc/ha, with 1553.33 kg / ha, and in turn achieved the highest economic benefit per hectare-